The Brexit Dynamics: British and EU27 Challenges After the EU Referendum - Paul J. J. Welfens; David Hanrahan (Intereconomics, 2017)
Prior to the Brexit referendum, the UK government sent an information brochure to households across the country. Surprisingly, key findings of a study by the UK Treasury – including an expected per capita income loss of 1800 – were not included in the brochure. Calculations indicate that if this information had been included, the outcome of the referendum would have been 52.1% for Remain. Instead, the pro-Brexit campaign utilised anti-immigrant rhetoric to create a scapegoat for the under-provision of local public services, when actually this was due to massive cuts in budget transfers to local communities after the financial crisis. Looking ahead, major reforms are now necessary if the EU is not to disintegrate. Given the fresh support in the UK and US for banking deregulation, the EU must stand firm in support of prudential supervision and banking regulation to prevent a new international banking crisis.
Keywords: 330